CX08005, a Protein Tyrosine Phosphatase 1B Inhibitor, Attenuated Hepatic Lipid Accumulation and Microcirculation Dysfunction Associated with Nonalcoholic Fatty Liver Disease - Jiang Li; Xiaolin Zhang; Jinying Tian; Juan Li; Xuechen Li; Song Wu; Yuying Liu; Jingyan Han; Fei Ye (MDPI AG, 2023)
Nonalcoholic fatty liver disease (NAFLD) is one of the common metabolic diseases characterized by hepatic lipid accumulation. Insulin resistance and microcirculation dysfunction are strongly associated with NAFLD. CX08005, an inhibitor of PTP1B with the IC50 of 0.75 ± 0.07 μM, has been proven to directly enhance insulin sensitivity. The present study aimed to investigate the effects of CX08005 on hepatic lipid accumulation and microcirculation dysfunction in both KKAy mice and diet-induced obesity (DIO) mice. Hepatic lipid accumulation was evaluated by hepatic triglyceride determination and B-ultrasound analysis in KKAy mice. Insulin sensitivity and blood lipids were assessed by insulin tolerance test (ITT) and triglyceride (TG)/total cholesterol (TC) contents, respectively. In addition, the hepatic microcirculation was examined in DIO mice by in vivo microscopy. The results showed that CX08005 intervention significantly reduced the TG and echo-intensity attenuation coefficient in the livers of KKAy mice. Furthermore, we found that CX08005 treatment significantly enhanced insulin sensitivity, and decreased plasma TG and/or TC contents in KKAy and DIO mice, respectively. In addition, CX08005 treatment ameliorated hepatic microcirculation dysfunction in DIO mice, as evidenced by increased RBCs velocity and shear rate of the blood flow in central veins and in the interlobular veins, as well as enhanced rate of perfused hepatic sinusoids in central vein area. Additionally, CX08005 administration decreased the adhered leukocytes both in the center veins and in the hepatic sinusoids area. Taken together, CX08005 exhibited beneficial effects on hepatic lipid accumulation and microcirculation dysfunction associated with NAFLD, which was involved with modulating insulin sensitivity and leukocyte recruitment, as well as restoration of normal microcirculatory blood flow.